METHODS AND DIDACTIC GAMES USED IN ORGANIZING CORRECTIONAL-PEDAGOGICAL WORK WITH BLIND CHILDREN (European Journal of Pedagogical Initiatives and Educational Practices, 2024)
The article highlights the importance of using various visual and game methods to interest children with visual impairments in activities. Direct interest in game actions is described as gradual transition to interest in mental operations and tasks. At the same time, a number of method and didactic games are recommended.